Learners’ Reflective Practice between the Repeated Performances of Tasks: Effects on Second Language Development - Khezrlou, Sima (Dutch Journal of Applied Linguistics, 2021)
This study attempted to explore the role of reflection in the accurate use of the English regular past tense structure using task repetition. Thirty-one learners were assigned into two conditions: task repetition only (TR) and task repetition with self-reflection (TR+SR). Both groups repeated an oral narrative task two times and then carried out a new task of the same type (i.e., another oral narrative task). However, only the TR+SR learners were engaged in self-reflection through responding to a questionnaire developed for the purpose of this study. Results revealed that learners’ reflection on their first task performance helped them notice the gap between their existing and target structure use as attested by their significantly high scores in the repeated tasks as well as the new task. The results therefore indicate the potential of reflective practice as an effective intervention strategy between repeated performances of the same task in terms of accuracy.